2008
DOI: 10.1007/s11433-008-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface pore tension and adsorption characteristics of polluted sediment

Abstract: Most natural sediment particles have numerous pores and a complex surface texture which facilitates their adsorption of contaminants. Particle surface structure, therefore, is an important instrumental factor in the transport of contaminants, especially in water environments. This paper reports on the results of adsorption-desorption experiments to analyze polluted sediment surface pore tension characteristics performed on samples from the bottom of Guanting Reservoir. In our analysis, the Frenkel-Halsey-Hill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In the region of relative pressure from 0 to 0.8, the adsorption of nitrogen by both carbon black and particles increases with the increase of relative pressure, and the adsorption increases sharply after the relative pressure exceeds 0.8. From the shape of the adsorption isotherm, the trend of nitrogen adsorption by carbon black and sample particles classified as type II isotherm adsorption, which is the case of adsorption in multiple layers of porous media, similar to the findings of (Fang et al 2008). The sharp increase in adsorption at relative pressures approaching 1 is primarily attributed to the capillary condensation of nitrogen within the pores of the particles.…”
Section: Resultssupporting
confidence: 75%
“…In the region of relative pressure from 0 to 0.8, the adsorption of nitrogen by both carbon black and particles increases with the increase of relative pressure, and the adsorption increases sharply after the relative pressure exceeds 0.8. From the shape of the adsorption isotherm, the trend of nitrogen adsorption by carbon black and sample particles classified as type II isotherm adsorption, which is the case of adsorption in multiple layers of porous media, similar to the findings of (Fang et al 2008). The sharp increase in adsorption at relative pressures approaching 1 is primarily attributed to the capillary condensation of nitrogen within the pores of the particles.…”
Section: Resultssupporting
confidence: 75%
“…Xue et al [29] studied multifractal characteristics of pores in soil based on experimental data measured by mercury intrusion methods. Fang et al [30] calculated the fractal dimension according to different model based on nitrogen adsorption and desorption experiments. Zhou et al [31] quantified the complexity of the flow boundary by introducing the fractal dimension of boundary shape.…”
mentioning
confidence: 99%
“…However, we had measured the porosity and pore size distributions of the same sediment samples from Guanting Reservoir by the gas adsorption method. The average pore sizes of those samples were in the range of 2 to 50 nm, with the largest pore volume being 3.7 nm in size [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pores of sediment particles increase the specific surface area, and large specific surface area greatly enhances the physical and chemical effects on the microinterface (solid-liquid interface). We previously reported that the adsorption of phosphorus onto sediments decreases the volume of pores smaller than 10 nm by filling these pores with contaminants [ 17 ]. Luo et al [ 19 ] also found that the fill of Enano-TiO2 particles into the micropores of sediments could significantly reduce t-Plot micropore specific surface area and cause slight decrease in sediment P binding energy.…”
Section: Resultsmentioning
confidence: 99%